2020
DOI: 10.1016/j.amjoto.2020.102639
|View full text |Cite
|
Sign up to set email alerts
|

Subjective smell and taste changes during the COVID-19 pandemic: Short term recovery

Abstract: Since the COVID-19 pandemic began, many individuals have reported acute loss of smell and taste. In order to better characterize all patients with these symptoms, a longitudinal national survey was created. Since April 10, 2020, 549 completed the initial survey, with 295 completing 14-day, and 202 completing 1-month follow up surveys. At 1-month follow-up, 71.8% reported a return to "very good" or "good" smell, and 84.2% reported a return to "very good" or "good" taste. Chemosensory changes are a cardinal sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 13 publications
3
41
1
1
Order By: Relevance
“…SARS-CoV-2 entry is mediated via Angiotensin Coverting Enyzme 2 (ACE-2) and Transmembrane serine protease 2 (TMPRSS-2) receptors present throughout the olfactory cleft, with associated inflammatory disruption of the nervous system via nasal olfactory fibers [ 17 ]. Symptoms often persist for 4–6 weeks, affecting patients' overall quality of life [ [18] , [19] , [20] ]. While early studies demonstrate a high rate of spontaneous resolution, the residual 10% with persistent olfactory dysfunction underscore the tremendous need for improved treatment options [ 21 ].…”
Section: Taste and Smellmentioning
confidence: 99%
“…SARS-CoV-2 entry is mediated via Angiotensin Coverting Enyzme 2 (ACE-2) and Transmembrane serine protease 2 (TMPRSS-2) receptors present throughout the olfactory cleft, with associated inflammatory disruption of the nervous system via nasal olfactory fibers [ 17 ]. Symptoms often persist for 4–6 weeks, affecting patients' overall quality of life [ [18] , [19] , [20] ]. While early studies demonstrate a high rate of spontaneous resolution, the residual 10% with persistent olfactory dysfunction underscore the tremendous need for improved treatment options [ 21 ].…”
Section: Taste and Smellmentioning
confidence: 99%
“…The loss and dysfunction of olfaction due to SARS-CoV-2 has been reported to recover within weeks [5]. However, many studies have identified long-term complications of olfaction [4,6]. Clinical studies have observed elevated levels of pro-inflammatory TNF-α in the olfactory epithelium of COVID-19 positive individuals [9].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective review across 169 COVID-19 patients by Yan et al [3] reported outpatient care to be strongly and independently associated with anosmia (the complete loss of smell). Agyeman et al [4] further reported 41% of 8438 COVID- 19 positive individuals experienced olfactory dysfunction. For the majority of individuals who experience distortions in olfaction, they tend to recover this sense within a month [5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…After participants signed the informed consent, a self-administered structured questionnaire were collected, including age, sex, underlying diseases, possible hospital associated risk factors, community associated risk factors, travel history, possible COVID-19 associated symptoms (fever, cough, taste or olfactory change). 7 , 8 The hospital associated risk factors were defined as working at COVID-19 ward, or short distance taking care of COVID-19 patients (defined as <1.5 m), or perform oropharyngeal/nasopharyngeal swab sampling for suspected or confirmed COVID-19 patients. The community associated risk factors were defined as recent clinic visit within 3 months, family/friends with possible COVID-19 associated symptoms (fever, cough, taste or olfactory change) within 3 months, or family with international travel history.…”
Section: Methodsmentioning
confidence: 99%